2004
DOI: 10.1159/000076343
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Fluvoxamine as a Treatment for Behavioral Symptoms in Frontotemporal Lobar Degeneration Patients

Abstract: Patients with frontotemporal lobar degeneration (FTLD) present a profound personality change, social misconduct, overeating, and stereotyped behavior. We examined the hypothesis that many of the behavioral symptoms of FTLD will respond to selective serotonin reuptake inhibitors (SSRIs). Sixteen FTLD patients were treated with an SSRI (fluvoxamine maleate) in an open 12-week trial. Treatment responses for stereotyped behavior and other neurobehavioral symptoms were evaluated by the Stereotypy Rating Inventory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 23 publications
2
56
0
3
Order By: Relevance
“…118 In an open label study with fluvoxamine, improvement in the stereotypy inventory (p< 0.01) and NPI (p<0.05) were noted. 119 For the management of cognitive symptoms related to FTD, several open label studies have demonstrated benefit in patients who were treated with NMDA antagonist (memantine) with doses up to 20mg/day. 120 In an open label study of 16 121 However a recent RCT of 81 patients did not demonstrate a clear benefit with NMDA antagonist (memantine).…”
Section: Frontotemporal Dementiamentioning
confidence: 99%
“…118 In an open label study with fluvoxamine, improvement in the stereotypy inventory (p< 0.01) and NPI (p<0.05) were noted. 119 For the management of cognitive symptoms related to FTD, several open label studies have demonstrated benefit in patients who were treated with NMDA antagonist (memantine) with doses up to 20mg/day. 120 In an open label study of 16 121 However a recent RCT of 81 patients did not demonstrate a clear benefit with NMDA antagonist (memantine).…”
Section: Frontotemporal Dementiamentioning
confidence: 99%
“…The change in the total NPI pre-and post-treatment was compared with a random effects model as previously described. 7 Some studies used the 10-item NPI, 8,9 and some used the 12-item NPI. [10][11][12][13] However, when these studies were grouped separately in the meta-analysis, the difference in the average NPI difference was minimal (−15.5 vs −15.2) and so these two groups were combined for the reported meta-analysis.…”
Section: Meta-analysismentioning
confidence: 99%
“…The serotonergic and dopaminergic functions were decreased in the hypothalamus and frontal and temporal lobes in FTD [11,12,[15][16][17] and serotonin dysfunction could correlate with food preferences for bananas, or sweet cravings, obsessive-compulsive behavior, disinhibition and aggression [18][19][20] , in addition to depression, irritability and apathy [13,21,22] . SSRIs have been tried in an open-label (OL) application in FTD patients, improving some of the obsessive symptoms [23][24][25] , but a placebo-controlled trial of paroxetine was negative and even found deterioration of cognition [26] . Serotoninergic trazodone has been found to be efficacious in a placebo-crossover design to improve behavior in FTD [27] .…”
Section: Galantamine In Frontotemporal Dementia and Primary Progressimentioning
confidence: 99%